Stability of pharyngeal airway space after maxillomandibular advance surgery in patients with class II malocclusion (Revista da Faculdade de Odontologia - UPF, 2011)
The lateral cephalometric radiographs show a high degree of visual resolution for the pharyngeal airway space, which is delimited by soft and hard tissues. Oromaxillofacial surgical treatment may be indicated for the patient with skeletal class II malocclusion, where whether or not mandibular advance is associated with interventions of the maxilla. Objective: The objective of this study was to determine the stability of the dimensional alterations of the total pharyngeal airway space (TPAS), distinguishing the airway space of the nasopharynx (NP), oropharynx (OP) and hypopharynx (HP), in cm2, after maxillomandibular advance. Methods: Cephalometric radiographs were taken in the preoperative (PRE), early postoperative (EPOST) and late postoperative (LPOST) periods of patients who submitted to combining surgeries. Based on proposals of cephalometric studies for this area, a statistical analysis was accomplished to determine the presence or absence of significant differences between PRE and EPOST, between EPOST and LPOST, and between PRE and LPOST. Results: There was an increase in values of the OP area and of TPAS in EPOST and decrease in LPOST. However, for these airway spaces, area values in LPOST differed from those in PRE, which were always much lower. Conclusions: These results may contribute to the treatment of obstructive sleep apnea and hypopnea, even if relapse occurs, where the pharyngeal airway space is still greater in LPOST than in PRE.